The new Project 4 Public Market exploring a hybrid market typology - Sabarre, Mickaela Alexandra; De Leon, Ruby Teresa M. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
For the longest time, public markets have been the primary trading centers in cities and municipalities in the country. However, they have struggled to keep up with the emergence of supermarkets, convenience stores, and just recently, online shopping. The Project 4 Public Market, currently facing the threat of gentrification of Project 4, is only one of the many markets that struggle to stay relevant in the changing urban fabric of their neighborhood.
With that arises the problem, “What architectural design can enhance the public market culture of Project 4, and elevate it into a new and adaptive building typology?”
The researcher reaches the hypothesis that in order to yield the best possible design of the new Project 4 Public Market, it should be able to answer to the needs of its users. Moreover, the researcher makes use of placemaking strategies by conducting a survey among the stakeholders of the new Project 4 Public Market to determine and take into consideration their needs in designing for the market. Special attention will be given to vertical urbanism
due to the limitations of the site. This will be accompanied by surveys and interviews with the stakeholders (vendors, shoppers, administration, etc.). The end goal of this study is to be able to redesign the public market’s structure for it to be more sustainable for the community it inhabits.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Markets -- Project 4 (Quezon City)